OP0082 Fibrosis and microangiopathy are the main histopathological hallmarks of scleroderma-related myopathy. (15th June 2017) - Corallo, C; Cutolo, M; Soldano, S; Volpi, N; Franci, D; Montella, A; Chirico, C; Nuti, R; Giordano, N
Abstract : Background: Systemic sclerosis (scleroderma, SSc) is an autoimmune connective tissue disease characterized by skin and internal organ fibrosis, coupled with widespread vascular pathology. Skeletal muscle involvement in SSc has often been considered as a minor component of the disease associated with disuse. Objectives: The goal of this study is to identify specific histopathological hallmarks of skeletal muscle involvement in SSc. Methods: A total of 50 SSc patients presenting clinical, serological and electromyographic (EMG) features of muscle weakness, were enrolled. Patients underwent vastus lateralis biopsy, assessed for individual pathologic features including fibrosis [type I collagen (Coll-I), transforming growth factor β (TGF-β)], microangiopathy [cluster of differentiation 31 (CD31), pro-angiogenic vascular endothelial growth factor A (VEGF-A), anti-angiogenic VEGF-A165b], immune/ inflammatory response [CD4, CD8, CD20, human leucocyte antigens ABC (HLA-ABC)], and membranolytic attack complex (MAC). SSc biopsies were compared to biopsies of ( n =50) idiopathic inflammatory myopathies (IIMs) and to ( n =50) noninflammatory myopathies (NIMs). Ultrastructural abnormalities of SSc myopathy were also analyzed by transmission electron microscopy (TEM). Results: Fibrosis in SSc myopathy (90%) is higher compared to IIM (30%, p <0.05) and to NIM (15%, p <0.05). Vascular involvement is dominant in SSc muscle (95%), and in IIM (75%) compared to NIM (20%, p <0.05). In particular, CD31 shows loss of endomysial vessels in SSc myopathy with respect to IIM ( p <0.05) and to NIM ( p <0.01). VEGF-A is downregulated in SSc myopathy compared to IIM ( p <0.05) and to NIM ( p <0.05), while VEGF-A165b is upregulated in SSc myopathy. The SSc immune/inflammatory response suggested humoral process with majority (80%) HLA-ABC fibral neoexpression and complement deposits on endomysial capillaries MAC, compared to IIM ( p <0.05), characterized by CD4+/CD8+/B-cell infiltrate, and to NIM ( p <0.05). TEM analysis showed SSc vascular alterations consisting of thickening and lamination of basement membrane and endothelial cell 'swelling' coupled to endomysial/perimysial fibrosis. Conclusions: The predominat features of SSc-related myopathy are fibrosis, microangiopathy and humoral immunity. However, it is difficult to identify specific histopathological hallmarks of muscle involvement in SSc, since they could be present also in other (IIM/NIM) myopathies. Disclosure of Interest: None declared